2021
DOI: 10.3390/su132313056
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-Temporal Characteristics of Arctic Summer Climate Comfort Level in the Context of Regional Tourism Resources from 1979 to 2019

Abstract: In the context of global warming, a key scientific question for the sustainable development of the Arctic tourism industry is whether the region’s climate is becoming more suitable for tourism. Based on the ERA5-HEAT (Human thErmAl comforT) dataset from the European Center for Medium-range Weather Forecasts (ECMWF), this study used statistical methods such as climatic tendency rate and RAPS to analyze the spatial-temporal changes in Arctic summer climate comfort zones from 1979 to 2019 and to explore the influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Similarly, research by Mohammed in North Africa and the Middle East found UTCI values ranging from 0 • C to 32 • C, with an increasing trend of 0.1 • C to 0.7 • C decade −1 [28]. In the Arctic, the average UTCI was found to be 0.025 • C, and it has shown a significant increase at a rate of 0.457 • C decade −1 during the summer [29]. In Russia, thermal stress ranges from extreme cold stress to moderate heat stress in summer, and the distribution and trend of thermal stress are primarily related to air temperature.…”
Section: Introductionmentioning
confidence: 79%
“…Similarly, research by Mohammed in North Africa and the Middle East found UTCI values ranging from 0 • C to 32 • C, with an increasing trend of 0.1 • C to 0.7 • C decade −1 [28]. In the Arctic, the average UTCI was found to be 0.025 • C, and it has shown a significant increase at a rate of 0.457 • C decade −1 during the summer [29]. In Russia, thermal stress ranges from extreme cold stress to moderate heat stress in summer, and the distribution and trend of thermal stress are primarily related to air temperature.…”
Section: Introductionmentioning
confidence: 79%
“…In order to explore the linear trends of Tmax and HWEs, linear regression was carried out. It has been a common method to determine the long-term linear trend of a certain meteorological variable [47,48]:…”
Section: Regression Analysismentioning
confidence: 99%
“…The UTCI has many advantages and shortcomings (Błażejczyk et al 2012 ; Błażejczyk and Kuchcik 2021 ). Among other considerations, the UTCI has important advantages: (i) it is expressed in °C—a unit of measurement that is understandable not only to specialists, but also to the broader public; and (ii) it can be used in a huge temperature range from below −50°C and up to higher than +50°C (Błażejczyk et al 2012 ; de Freitas and Grigorieva 2017 ; Błażejczyk and Kuchcik 2021 ) and applied around the world, enabling direct comparisons of results for different areas: in Europe (Antonescu et al 2021 ), in the Caribbean (Di Napoli et al 2022 ), in the Arctic (Mölders 2019 ; Shartova et al 2019 ; Huang et al 2021 ), China (Mi et al 2020 ; An et al 2021 ; Wang and Yi 2021 ; Liu et al 2022 ), Japan (Ohashi et al 2018 ), Russia (Shartova et al 2019 ; Konstantinov et al 2020 ; Vinogradova 2021 ). The UTCI has been used in a variety of applications (Krüger 2021 ), including medical science (Shartova et al 2019 ; Urban et al 2021 ; Romaszko et al 2022 ), tourism (Huang et al 2021 ), and in urban planning (Krüger 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Vinogradova ( 2021 ) evaluated climatological and extreme values of the UTCI for a network of surface stations in Russia, but temporal variations and trends were not considered. Huang et al ( 2021 ) documented Arctic-averaged variations of the UTCI computed from the ERA5 reanalysis, but study area was limited to 65–90°N, and most of results were presented as averages over all or parts of the land areas north of 65° N.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation